Penerapan Jaringan Tethering Wifi Android untuk Mengakses Informasi Studi Kasus: Karang Taruna Kerawang - Rachmatsyah, Agus Dendi (Sekolah Tinggi Manajemen Informatika dan Komputer PalComTech, 2017)
Computer network is a collection of computer devices connected to one, while the Internet network is a collection of computer networks that are connected globally. Android is an operating system used for smartphone devices, while thetering is a utilization hostspot internet using existing facilities on the smartphone. Problems that occur is still a lot of young people, especially Karang taruna who do not know the tethering network, so still limited using external modem. The research method used by experiment Â building tethering network, by doing the workshop directly together with Karang Taruna RW 09 Karang Pawitan. From the conclusion obtained that the making of tethering network is very easy to be applied by anyone, where users do not have to buy additional modem device again on the laptop but only using the devices available on smartphones with android operating system other than it can be used by more than two user users, Different from a modem that can only be used for one laptop device.Keywords : Internet, Android, Tethering